Environment in Times of War Climate and Energy Challenges in the Post-Soviet Region - Ferrari, Aldo (ISPI Publications, 2022)
The impact of Russia's war against Ukraine has been devastating both politically and environmentally. On top of the environmental damage directly caused by military operations, the invasion has put an abrupt end to the EU-Russia "green cooperation", which had previously raised many hopes. At the same time, it has also shifted international attention away from climate and environmental concerns, which are particularly acute in the post-Soviet region. This Report analyses some of the main climate change and environmental issues in the post-Soviet space, providing an initial assessment of the invasion's impact. The bulk of the latest scholarly and policy production on these matters focuses on Russia - given the country's geopolitical and energy relevance. However, this analysis finds that environmental disasters such as the desertification of the Aral Sea transcend state borders and require a broader approach both from an analytic and policy standpoint.